(untitled) (Journal of Human Sciences, 2020)
Human concepts emerged imposed by civilizational variables, intermingling with different cultures, and massive social transformations in literature in general and poetry in particular, and among these phenomena is the poetry of complaint, and the objective conditions and the self-readiness of each poet to depart from the patterns of tradition are factors that led to the expansion of the circle of literary issues and to adopting literary expression A tool for a large movement of cash. The poetry of the complaint is a modern and renewed art, which has its roots in ancient times and has huge implications for human societies in its diversity and has its spread on the level of the poets of society with different sects, doctrines and nationalities, because it is an expression of the hidden human pain, painful sorrows, and problems that he faces in life, whether psychological, social, or psychological. The poets ’view of the complaint differs, each according to his culture and age, and this is natural due to the circumferential and ground-based differences of sophistication and depth. Each has his own sense, creative energy and verbal connotations that are shaped by the sincerity of experience. The poetic experience of Al-Huni’s poetry is one of the most prominent experiences evident in his poetry (Escape within the Self), through which it became clear that his life experience is difficult due to the conditions of mobility and poverty, because he was able, however, to defeat time and persevere in forming himself by learning inside and increasing knowledge abroad, but he In all stages of his life, he was connected to his land (the south) and to the problems of his reality in terms of clarity and comprehensiveness. One of the most important characteristics of the poetry of the complaint of the poet (Al Huni) was to define his position on the conflict that is taking place in a society, and that every creative process on his part stands on the side of a class of conflicting groups. The question that arises is to what extent has the Huni poet succeeded in addressing emotional and social dilemmas through the poetry of complaint? We do not try to offer solutions through the poet’s poetry; But we try to find out what distinguished his poetic experience through the complaint axes. The research will initially attempt to arrive at a specific concept of the complaint by discussing it in terms of linguistic and idiomatic (social) terms, then moving to the practical and analytical side by approaching the subjects of the complaint and linking its context to the general public. In which the society is separated from its members, from time and place ... and the intellectual complaint that discusses the individual’s separation from the culture of his society, present and past.